Origin of different thermal cycling effects in Fe80P20 and Ni60Nb40 metallic glasses. (March 2021) - Tang, Y.; Zhou, H.F.; Wang, X.D.; Cao, Q.P.; Zhang, D.X.; Jiang, J.Z.
Abstract: The effect of thermal cycling on structure and properties has been explored in many metallic glasses (MGs) within last 5 years. It is critical to establish the connection between macroscopic mechanical response and the underlying atomic level process during thermal cycling. The mechanisms underlying the complexity of thermal cycling effect are poorly understood. Here, we investigate the thermal cycling effect on structural evolution and property changes in brittle Fe80 P20 and ductile Ni60 Nb40 MGs. Our results demonstrate that thermal cycling treatment initially delays the cavitation behavior for Fe80 P20 MG and induces local-to-non-localized deformation mode change with high probability for N60 Nb40 MG, despite their opposite atomic structural evolution. Specifically, with initial thermal cycling, the Fe80 P20 MG prefers to relax, while Ni60 Nb40 MG prefers to rejuvenate. With further thermal cycling, the Fe80 P20 MG rejuvenates while Ni60 Nb40 relaxes back towards a relative stable state. To reveal the origin of such opposite thermal cycling effects in these MGs, we proposed 'core-shell' structural models of MGs. Our results shed light on the atomistic understanding of the relationship between the micro-structure and thermal cycling effect in MGs, which may offer useful insights for designing and processing MGs. Graphical abstract: Image 1 Highlights: A detailed description and explanation of thermal cycling effects on structure and properties for brittle Fe80 P20 and ductile Ni60 Nb40 MGs, has been obtained. The mechanical properties of Fe80 P20 and Ni60 Nb40 MGs could be improved at small cycles, but the evolution of 'open volume' atoms are very different. The thermal cycling effect on a MG depends on the total contribution of rejuvenation in densely-packed shells and relaxation in loosely-packed cores.